2020
DOI: 10.1021/acs.jproteome.0c00560
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lipids for Early Triage and Dose Estimation after Acute Radiation Exposure in Rat Plasma Based on Targeted Lipidomics Analysis

Abstract: Rapid early triage and dose estimation is vital for limited medical resource allocation and treatment of a large number of the wounded after radiological accidents. Lipidomics has been utilized to delineate biofluid lipid signatures after irradiation. Here, high-coverage targeted lipidomics was employed to screen radiosensitive lipids after 0, 1, 2, 3, 5, and 8 Gy total body irradiation at 4, 24, and 72 h postirradiation in rat plasma. Ultra-performance liquid chromatography–tandem mass spectrometry with a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several untargeted lipidomic studies have investigated irradiation effects in several models including cell cultures [23], murines [12,[24][25][26], NHPs [27][28][29], and humans [30] while the initial targeted lipidomic studies have primarily been limited to commercially available kits or eicosanoid profiling [31][32][33][34][35]. More recently, targeted lipid studies utilizing multiplex MRM assays showed that combinations from 416 lipids in blood could be used for modelling IR exposure between 4-72 h for 0-8 Gy in rats with excellent sensitivity and specificity [36]. As we typically see an increased number of lipid compounds changes post-irradiation in serum vs. polar compounds, we chose to utilize a targeted lipidomics approach in the current study.…”
Section: Targeted Lipidomics: Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Several untargeted lipidomic studies have investigated irradiation effects in several models including cell cultures [23], murines [12,[24][25][26], NHPs [27][28][29], and humans [30] while the initial targeted lipidomic studies have primarily been limited to commercially available kits or eicosanoid profiling [31][32][33][34][35]. More recently, targeted lipid studies utilizing multiplex MRM assays showed that combinations from 416 lipids in blood could be used for modelling IR exposure between 4-72 h for 0-8 Gy in rats with excellent sensitivity and specificity [36]. As we typically see an increased number of lipid compounds changes post-irradiation in serum vs. polar compounds, we chose to utilize a targeted lipidomics approach in the current study.…”
Section: Targeted Lipidomics: Serummentioning
confidence: 99%
“…Polyunsaturated (PUFA) CEs, typically containing 18:2, 20:4, or 22:6 acyl chains, can also be enzymatically or non-enzymatically oxidized and can form more complex peroxides [40]. Previous experiments have reported perturbation to CE(20:4) and CE(22:6) levels at higher doses in NHPs (10 Gy) and rats (8 Gy) [27,36] with a temporal change in NHPs showing lower concentrations at earlier time points (4 h), then increasing at later time points (7-10 d) [28]. These changes may be partially dose rate dependent, as in this study we observed increases in CE(22:6) at 1 d following the reference dose rate exposure and a decrease in CE(20:4) following the VHDR exposure (Supplementary File S1).…”
Section: Targeted Lipidomics: Serummentioning
confidence: 99%
“…Modifications of radiation effects can be observed by lipid peroxidation [152]. Radiation biodosimetry is another developing field and radiation-responsive lipids biomarkers identified in lipidomics studies are important in this development [153]. A recent study has investigated seven radiation-responsive lipids, including PC (18:2/18:2), PC (18:0/18:2), Lyso PC 18:1, PC (18:0/20:4), SM (D18:0/24:1), PC (16:0/18:1), and Lyso PC 18:2 which are useful in radiation biodosimeters [154].…”
Section: Lipidomicsmentioning
confidence: 99%
“…Glycerophospholipids (GP) and sphingolipids (SL) that include a choline group have essential structural and signaling functions [ 14 , 15 ]. These classes of lipids were already shown to be affected in response to ionizing radiation, both local body RT in humans [ 16 ] and whole-body irradiation in rodents [ 17 ]. Our previous study on lipid mass profiling documented that serum levels of different phospholipids were affected in samples of HNSCC patients treated with IMRT using the continuous accelerated irradiation (CAIR) scheme.…”
Section: Introductionmentioning
confidence: 99%